Determination of Flavonoids, Phenolic and Total Antioxidant Content from the Leaves, Stems and Roots of Betel Plants - Yefrida; Harsita, Wanda Dwi; Refilda (Jurnal Kimia Unand, 2025)
Betel (Piper betle L.) is one of the medicinal plants widely used in traditional medicine for its therapeutic properties. This study aimed to determine the levels of total flavonoids, phenolics, and antioxidants in the leaves, stems, and roots of four betel species, namely, Piper betle L., Piper ornatum N.E. Br., Peperomia pellucida (L.) Kunth, and Piper aduncum L. The Total Flavonoid Content (TFC) was measured using the aluminum chloride (AlCl₃) colorimetric method, while Total Phenolic Content (TPC) was determined using the Folin–Ciocalteu method. The antioxidant capacity was assessed by the 2,2-diphenyl-1-picrylhydrazyl (DPPH). The results showed that the highest TFC was found in Peperomia pellucida (L.) Kunth leaves (79.27 ± 1.37 mg QE/g DW), whereas the highest TPC was observed in Piper betle L. stems (23.97 ± 0.04 mg GAE/g DW). The strongest antioxidant capacity was also observed in Peperomia pellucida (L.) Kunth leaves (23.93 ± 0.36 mg AAE/g DW). Correlation analysis revealed a very strong relationship between TFC and antioxidant capacity in leaves (r = 0.9892) and a strong correlation between TPC and antioxidant capacity in roots (r = 0.9745). These findings suggest that the antioxidant potential of betel species is closely related to their secondary metabolite composition, particularly flavonoids and phenolic compounds.